Congress volume : Oslo 1998 - Lemaire, André, 1942-; Sæbø, Magne. (Supplements to Vetus Testamentum,, 2000)
This Congress Volume comprises not only the main lectures of the XVIth I.O.S.O.T. Congress, held in Oslo 1998, but also the interventions at the two panels on \'Intertextuality and the Pluralism of Methods\' and on \'The Hebrew Bible and History\'. Both the main lectures and the panelists' interventions focus on current methodological problems and study central questions in the present study of the Hebrew Bible/Old Testament in its environment.